2007
DOI: 10.1111/j.1439-037x.2007.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contents of Vegetables Grown in Soil, Irrigated with Mixtures of Wastewater and Sewage Sludge in Pakistan, using Ultrasonic‐Assisted Pseudo‐digestion

Abstract: The success of risk assessment of metal-contaminated soils depends on how precisely one can predict the bioavailability of trace and toxic metals in soil and transfer to the human food chain. A field experiment was carried out from 2004 to 2005 to evaluate the long-term effect of sewage sludge application in agricultural lands where mostly vegetables are grown. The aim of this study was to predict the uptake of Cd, Cu, Cr, Ni, Pb and Zn by different vegetables grown on agricultural soil irrigated for long peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 31 publications
2
50
2
1
Order By: Relevance
“…[42] The high level of Cd in food commodities and drinking water is also one of the sources of Cd in our patients, most likely from rice and vegetables grown in soil dressed with untreated industrial waste water sludge. [43] During the past decade, several studies on the health effects of environmental exposure to Cd have shown that tubular effects occur at urinary cadmium concentrations of 1-2 mg/g creatinine. [44] As in our investigated results, a high level of Pb was observed in biological samples of CRFPs as compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[42] The high level of Cd in food commodities and drinking water is also one of the sources of Cd in our patients, most likely from rice and vegetables grown in soil dressed with untreated industrial waste water sludge. [43] During the past decade, several studies on the health effects of environmental exposure to Cd have shown that tubular effects occur at urinary cadmium concentrations of 1-2 mg/g creatinine. [44] As in our investigated results, a high level of Pb was observed in biological samples of CRFPs as compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the study showed that the concentration of Pb ranged between 0.016 to 1.387 mg/kg with the highest level recorded in G. africanum (1.387 mg/kg) followed by O. gratissimum (1.358 mg/kg) and T. occidetalis (1.163 mg/kg) all in Kpanshia market while the lowest level Pb was recorded in A. esculentus from Swali market (0.016 mg/kg). Cadmium concentration ranged from 0.028 to 1.487 mg/kg with the highest seen in T. triangulare (1.487) from Kpanshia market [31][32][33][34][35][36]. However, V. amygdalina from both markets and O. basilicum from Kpanshia market were below detectable limit (BDL<0.001).…”
Section: Concentration (Mg/kg) Of Heavy Metals In Selected Vegetablesmentioning
confidence: 99%
“…While remediation technologies for heavy metals (Mulligan et al 2001;Peng et al 2009) and polycyclic aromatic hydrocarbons (Bamforth and Singleton 2005;Zang et al 2007) are being developed, they are yet to see widespread application, owing both to technological and cost-effectiveness barriers. Despite the dominance of Chinese research, there also exists a substantial body of work on chemical contaminants interacting with urban agriculture elsewhere in Asia, including, inter alia, Vietnam (Huong et al 2010), India (Agrawal et al 2003;Gupta et al 2008;Singh et al 2009Singh et al , 2010, and Pakistan (Jamali et al 2007). Of course, heavy metals and PAHs from combustion and various other industrial processes in cities are not the only chemical contaminants of concern to urban agriculture.…”
Section: Pahs Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Such unceasing rural-to-urban migration and consequent falling average household incomes are generally agreed to be the main driving forces behind the believed expansion of urban agriculture in developing countries, although the precise contribution of urban agriculture to alleviating poverty has been difficult to quantify (Bryld 2003;Zezza and Tasciotti 2010). It has even been argued that for many developing countries, the Structural Adjustment Programs (SAPs) of the International Monetary Fund and the World Bank (The Bretton Woods Institutions), which are intended to increase household income through development of a well-managed free-market economy, have in fact led to a worsening fiscal situation for the urban poor, which in turn has driven greater reliance on urban agriculture (Bryld 2003;Demery and Squire 1996;Jamal 1985;Ratta and Nasr 1996).…”
Section: Introductionmentioning
confidence: 99%